Perencanaan dan Pemetaan Desa Lunjen, Kecamatan Buntu Batu, Kabupaten Enrekang - Firda Rahmayanti; Farid Asfari Rahman; Regina Shintya Dewi J; Mas Dadang Enjat Munajat; Evi Novianti (Politeknik Pariwisata Makassar, 2023)
This study aims to determine the tourist attraction and design a mapping model of the distribution of tourist attraction and amenity in Lunjen Village, Enrekang Regency by making a map of tourist attraction and amenity in Lunjen Village. This research model is applied so that the results can be implemented. Data collection was done through direct observation in the field accompanied by unstructured interviews and documentation. The result of the research is a map of the distribution of tourist attractions and amenities in Lunjen Village using ArcGis 10.8, which is used as an auxiliary medium for tourists in obtaining information about tourist attractions in Lunjen Village, Enrekang Regency. The conclusion in this study is the distribution of tourist attractions using ArcGis 10.8 can make it easier to see tourist attractions and amenity in Lunjen Village in the form of a map.